ROH KUDUS SEBAGAI SUBJECT MATTER DALAM PEMBELAJARAN PENDIDIKAN KRISTEN - Junihot M. Simanjuntak (Bethel Press, 2019)
This paper aims to describe the importance of understanding the role of the Holy Spirit wider, especially in Christian education learning. Wearing a descriptive-analytic method, the author describes the role of the Holy Spirit as the subject matter in Christian Education learning. Results: 1) The Holy Spirit is the Triune God, He is actively present as a subject and as an object that is learned in the learning of Christian Education, it was recognized by the Lord Jesus, the apostles, and fathers, as well as the practitioners of Christian education; 2) The Holy Spirit inhabit Christian teachers and learners to form human beings who have spiritual strength, self-control, the maturation of personality, intelligence, noble character, and skills that are needed.